Metropolitan Marvels : To Forge Seamless Possibilities for Urban Discoverability and Connectivity - Shree B, Divya; R, Disha; Ms. Sreelatha; Vishwakarma, Shivangi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Embodies a particular approach with the devising set out to enrich the quality of the city living experience incorporating technology and real human relationships in applying information in the city. The research journey is going to trace dynamic pathways underpinning in software development through powerful tools like Android Studio among others that helps in designing simple and user-friendly interfaces that easily adjust themselves to the diversity of the residents who live in cities and visitors come to the city. It now focuses to build proper links of implementation not on the technological strides but only by increasing the spotlight. Reliability as well as availability is ensuring that hustling has a strong back-end that would handle the data smoothly by the use of applications like Firebase and Room Persistence. Added to it, the approach makes use of offline capabilities as well part of validation of strict security precursors for performing through real-user trials while designing the likes of the application in conformance to the changing user preferences of the urban communities. This methodology visualizes transformative fostering of people-centric cities in successfully intricacy technology by richness of human experiences within innovative city information application, and elevated urbanlifestyles.
Keywords: Metropolitan Marvels; Forge Seamless; Firebase; Room Persistence